Silicon-Based 0.45-0.47 THz Series-Fed Double Dielectric Resonator On-Chip Antenna Array Based on Metamaterial Properties for Integrated-Circuits - Alibakhshikenari, Mohammad; Virdee, Bal Singh; See, Chan; Abd-Alhameed, Raed; Limiti, Ernesto (2019)
The antenna array designed to operate over 0.45-0.47 Terahertz comprises two dielectric resonators (DRs) that are stacked vertically on top of each other and placed on the surface of the slot antenna fabricated on a silicon substrate using standard CMOS technology. The slot created in the silicon substrate is meandering and is surrounded by metallic via-wall to prevent energy dissipation. The antenna has a maximum gain of 4.5dBi and radiation efficiency of 45.7% at 0.4625 GHz. The combination of slot and vias transform the antenna to a metamaterial structure that provides a relatively small antenna footprint.